2012
DOI: 10.1037/a0028613
|View full text |Cite
|
Sign up to set email alerts
|

Striving to connect: Extending an achievement goal approach to teacher motivation to include relational goals for teaching.

Abstract: Two studies were designed to extend Butler's (2007) model and measure of achievement goals for teaching, to recognize that teaching is an interpersonal endeavor, not just personal endeavor. In Study 1, results from 530 teachers in Israel confirmed the predicted 5-factor model comprising relational goals, whereby teachers aspire to create close and caring relationships with students, in addition to the previously identified mastery, ability-approach, ability-avoidance, and work avoidance goals for teaching. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
218
2
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(258 citation statements)
references
References 64 publications
(124 reference statements)
25
218
2
13
Order By: Relevance
“…In research, teacher motivation has been investigated mainly in terms of self-efficacy beliefs (e.g., Dicke et al, 2014;Klassen & Chiu, 2011;Moe, Pazzaglia, & Ronconi, 2010; see also Woolfolk Hoy, Hoy, & Davis, 2009) and goal orientations (e.g., Butler, 2007Butler, , 2012Klassen, Perry, & Frenzel, 2012;Nitsche, Dickh€ auser, Fasching, & Dresel, 2011;Retelsdorf, Butler, Streblow, & Schiefele, 2010). Less often has teacher motivation been examined in terms of intrinsic motivation (see Kunter & Holzberger, 2013;Roth, 2013) or (positive) affect Keller et al, 2014;Kunter et al, 2008).…”
Section: Journal Of Research In Science Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…In research, teacher motivation has been investigated mainly in terms of self-efficacy beliefs (e.g., Dicke et al, 2014;Klassen & Chiu, 2011;Moe, Pazzaglia, & Ronconi, 2010; see also Woolfolk Hoy, Hoy, & Davis, 2009) and goal orientations (e.g., Butler, 2007Butler, , 2012Klassen, Perry, & Frenzel, 2012;Nitsche, Dickh€ auser, Fasching, & Dresel, 2011;Retelsdorf, Butler, Streblow, & Schiefele, 2010). Less often has teacher motivation been examined in terms of intrinsic motivation (see Kunter & Holzberger, 2013;Roth, 2013) or (positive) affect Keller et al, 2014;Kunter et al, 2008).…”
Section: Journal Of Research In Science Teachingmentioning
confidence: 99%
“…In order to correctly estimate the standard errors in such a nested data structure as well as to differentiate effects occurring within and between classes, multilevel structural equation models (MSEM) were calculated utilizing the software Mplus 7.0 (Muthen & Muthen, 1998-2012. Teacher and student motivation as well as students' perceived enthusiastic teaching were modeled as latent variables, teacher pedagogical content knowledge, students' achievement and cognitive activation as manifest variables.…”
Section: Data Analysesmentioning
confidence: 99%
“…Additionally, further examination of the moderating effects of additional variables not explored in this study, such as school culture, cohort effects, leadership style, and personality-related factors, could also help to ascertain how and when these effects occur in real-world teaching contexts. Similarly, it is possible that other, more directly overlapping socio-cognitive variables not assessed in this study may to some extent account for the observed relationships, for example, the negative effects of horizontal comparisons on adjustment outcomes (e.g., competitiveness, belongingness, social goals; Bergin & Bergin, 2009;Butler, 2012;Van Ryzin et al, 2009). As such, it is anticipated that future research in which additional potential moderators or mediators of the relations between social comparisons and adjustment in teachers are examined may shed more light on the mixed findings in this study.…”
Section: Limitations and Future Directionsmentioning
confidence: 91%
“…Concerning existing research with teachers on constructs related to social comparisons, studies have found higher levels of collective selfefficacy, defined as the perceived confidence of an individual teacher in the collective capabilities of teachers as a group (e.g., Tschannen-Moran, Hoy, & Hoy, 1998), to correspond with greater student learning (Parker, Hannah, & Topping, 2006) and lower levels of burnout (Skaalvik & Skaalvik, 2007). Similarly, not unlike the observed emotional benefits of teachers' social goals reflecting a desire to connect emotionally with students (e.g., Butler, 2012;Butler & Shibaz, 2008), teachers who perceive a sense of relatedness to other teachers also report higher levels of instructional engagement and lower negative emotions (Klassen, Perry, & Frenzel, 2012). In addition, teachers are more likely to engage in upward comparisons with individuals whom they perceive as having attained desired achievable goals (Smith, 2000), or to individuals that inspire them (Kitchel et al, 2012).…”
Section: Social Comparisons In Teachersmentioning
confidence: 95%
“…Numerous studies underline the importance of these attitudes for their practical pedagogical work (see also e.g. Bless 1995;Butler 2012;de Boer et al 2011;Eberwein and Knauer 2009). Also, as Jordan et al (2008) rightly point out, teachers' inclusionary efficacy depends upon their beliefs about disabilities and their roles in working with students with special needs.…”
Section: Journal Of Studies In Educationmentioning
confidence: 99%